Avaliação da qualidade dos cuidados de enfermagem em um hospital universitário - Dias, Caren Franciele Coelho (2018)
This study aimed to evaluate the quality of nursing care in Clinic 1, 2 and 3 of a university hospital in the Southern Region of Brazil. It was developed in two stages. In the first one was developed a methodological research to adapt the instrument called "Active Search Record". Participants were three nurses participating in a research group and active in the research institution. This stage happened in September 2017. The results of the evaluation of the instrument by the evaluators were tabulated and analyzed according to agreement in Excel spreadsheet and analyzed through the software Statistic Package for Social Sciences. The data were examined by means of descriptive statistics, calculating the frequencies and percentages of agreement among the evaluators. In the second stage a descriptive and quantitative cross-sectional study was carried out to evaluate the quality of nursing care through the reformulated instrument. Participants were 390 patients admitted to the Clinical Unit 1, Clinic 2 and Clinic 3 and were collected from September 11 to December 4, 2017. This research was approved by the Research Ethics Committee of the UFSM with CAAE nº: 69979417.4.0000.5346. The instrument used has 15 indicators of quality of basic nursing care in the prevention of adverse events. The information was tabulated in an Excel spreadsheet and analyzed using the Statistic Package for Social Sciences software. These were analyzed, descriptively, evaluating the proportion of each indicator in the different clinics. Subsequently, a chi-square test of association was performed to verify if there was a significant difference in proportions. In order to classify the quality of care, the percentage of adequacy (percentage of positivity) was used, which classified care as safe, desirable, adequate, borderline or insufficient. The results of the first stage reached 100% concordance percentages, in relation to all the requirements for the indicators 6, 7, 9, 10, 12, 13 and 15. It was verified that the procedure with the lowest mean positivity was the indicator 8, with 75%. The other indicators presented satisfactory percentages of agreement. In the second stage, performed in Clinic 1, of the 15 indicators evaluated, none were described as Safe, and ten were characterized as Insufficient, were: indicator 1, 3, 4, 5, 6, 9, 12, 13, 14 and 15. In Clinic 2, no indicator was described as Safe, and nine were characterized as Insufficient, were: 1, 3, 4, 5, 6, 8, 9, 12 and 15. Clinic 3, nine indicators were considered Insufficient: 1, 4, 5, 6, 8, 9, 12, 14 and 15. Indicator 10 was the only one considered Safe, with 100% adequacy. The data presented show evidence that the instrument evaluated shows reliability to be applied in the studied units, assisting in the managerial practice of nurses. In the evaluated units, the performance in relation to the evaluated indicators was compromised, characterizing the need for investments in training, through attractive and stimulating ways, that propitiate the active search for knowledge and stimulate participation in the educational activities offered by the institution.